Bedding plant nutrition - Schrock, Patricia A. Tew, author; Goldsberry, Kenneth L., advisor (Colorado State University. Libraries, 1979)
Three nutrition experiments were conducted to determine the nitrogen, phosphorus, and potassium nutrient levels necessary to obtain quality bedding plant growth. A soil medium of equal parts (by volume) Fort Collins Clay Loam, Canadian peat moss, and perlite, and soilless medium of equal parts (by volume) Canadian peat moss and vermiculite were used in all experiments. Pelargonium hortorum 'Sprinter Scarlet' and Petunia hybrida 'Candy Apple' seedlings were grown in the 2 media and watered with 5 nutrient solutions containing varying ratios of NO3-:NH4+, each resulting in a total NO3- plus NH4+ concentration of 15 meq 1-1. There were no significant differences in height, fresh and dry weights, or number of vegetative breaks in soil-grown plants due to the N sources. Plant growth in the soilless medium was substantially reduced as the proportion of NH4+ increased above 50%. Plant quality of Pelargonium hortorum 'Sprinter Scarlet' and Petunia hybrida 'Candy Apple' were also evaluated in the 2 media when watered with 12 nutrient solutions containing 4 nitrogen concentrations (half NO3-, half NH4+) of 7.0, 11.5, 14.0, and 17.5 meq 1-1, and 3 potassium concentrations of 2, 4, and 6 meq 1-1. Potassium concentrations above 2 meq 1-1 had little or no affect on plant growth in either media. Increasing nitrogen rates caused increased plant height, and fresh and dry weights. The 7.0 meq 1-1 nitrogen-grown plants showed signs of nitrogen deficiency. Maturity, in terms of flowering and number of vegetative breaks, was not affected by the nutrient regime. Optimum plant growth in both media was produced with 11.5 meq 1-1 nitrogen and 2 meq 1-1 potassium treatment. Seedlings of Pelargonium hortorum 'Sprinter Scarlet', Petunia hybrida ' Pink Magic ', Impatiens holstii 'Elfin Red', and Tagetes patula 'Goldie' were grown in the 2 media with 4 phosphorus treatments consisting of 0 kg m-3 treble superphosphate preplant plus a continuous feed using 25-0-25 (1.408 meq 1-1 H2PO4-, 200 ppm P2O5), and 0, 3, and 6 kg m-3 treble superphosphate preplant plus a continuous feed of 20-20-20 (1.408 meq 1-1 H2PO4-, 200 ppm P2O5). All species, except impatiens, showed increased growth with increased phosphorus levels; impatiens gave little or no response to phosphorus treatments. Flowering time of all species was unaffected by the treatments. The 3 kg m-3 treble superphosphate plus a continuous feed of 20-20-20 (1.408 meq 1-1 H2PO4-, 200 ppm P2O5) gave the best plant response in both media.
Covers not scanned.
Keywords: Plants -- Nutrition